PERSEPSI MAHASISWA AKUNTANSI DAN PRAKTISI AKUNTANSI SYARIAH TERHADAP PARADIGMA, ETIKA, DAN KOMPETENSI PRAKTISI AKUNTANSI SYARIAH - Hendri Setyawan; Adhyaksa Rianristyadi (Jurnal Akuntansi Indonesia, 2013)
This study aims to: (1) to determine the differences in perceptions between students who have and who have followed the accounting courses accounting practitioners of Islamic sharia, (2) to determine differences in perceptions between students who have not taken an accounting class accounting practitioners Islamic sharia and the practitioners Islamic accounting, and (3) to determine differences in perceptions between students who have attended courses and practitioner of Islamic accounting accounting accounting practitioners Islamic sharia. Object of this study was the perception of students and practitioners of the Islamic accounting practitioners. In this research, the writer uses descriptive method and the T-Test using SPSS computer program. Results of data analysis and hypothesis testing is done by processing the data from the questionnaires distributed to  accounting students at Sultan Agung Islamic University, School of Economics Central Java, and the State Islamic Institute Wali Songo many as 99 people and practitioners of Islamic accounting in Islamic banks City Semaranng many as 27 people. Based on the analysis of data, it can be concluded that: (1) there are differences in perception between accounting students who have and have not been taking courses toward a paradigm of Islamic accounting, ethics, and competence of practitioners of Islamic accounting, (2) there are differences in perception between accounting students who have to take accounting courses and accounting practitioners of Islamic sharia on paradigms, ethics, and competence of practitioners of Islamic accounting, and (3) there are differences in perception between accounting students who have taken accounting courses and accounting practitioners of Islamic sharia on paradigms, ethics, and competence of practitioners of Islamic accounting.